The relationship between the green density and as-sintered density of nano-tungsten compacts. (November 2015) - Wang, Xu; Zak Fang, Z.; Koopman, Mark
Abstract: Tungsten is a primary candidate material for certain structural applications in future fusion reactors. However, drawbacks associated with these applications include the need for low ductile to brittle transition temperature (DBTT) and significant demands for fracture toughness. A possible solution to these problems is nanostructuring of tungsten (nano-W; grain size < 100 nm) following the conventional press-sinter route, which is quite economical. High green density and low temperature sintering are the critical factors for preserving nanoscale grains. Previous works, and our experience, have shown that it is nearly impossible to get high green density (> 40% relative density) of compacts for nano tungsten powders made by high-energy milling. This makes the material prone to rapid grain growth; with a grain size well over 100 nm before complete densification, even at 1000 °C. In this work, a high density green compaction method for nano-W powders was demonstrated, which can improve green density by at least 18% in relative density. Additionally, the effect of green density on the sintering behavior of nano-W was investigated. Highlights: Demonstrated a high density green compaction method for nano-tungsten powders Improved green density of nano-W powders by at least 18% in relative density The higher the green density achieved, the finer the grain size and the higher the final as-sintered densities were.